1995
DOI: 10.1099/0022-1317-76-7-1773
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of potato yellow mosaic geminivirus

Abstract: Mutations have been inserted into the virion and complementary sense ORFs encoding proteins with MrS in excess of 9 kDa of both DNA A and DNA B of potato yellow mosaic geminivirus (PYMV). Wild-type and mutant monomeric clones were tested for their ability to replicate, produce PYMV-specific DNA, spread and cause symptoms in Nicotiana benthamiana plants following biolistic inoculation. Dimeric clones of the DNA A mutants were also investigated by agroinoculation of leaf discs. In contrast to N. benthamiana plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Mutagenesis of TGMV illustrated that the AC2 ORF was r~'quired for symptom formation in whole plants but not viral I~NA replication in agroinoculated leaf discs [8] and the same r,~sult was found for PYMV [6]. The AC2 gene product of sttbgroup III geminiviruses can complement mutations in hete;ologous viral genomes both in protoplasts [10] and in plants [ i 1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis of TGMV illustrated that the AC2 ORF was r~'quired for symptom formation in whole plants but not viral I~NA replication in agroinoculated leaf discs [8] and the same r,~sult was found for PYMV [6]. The AC2 gene product of sttbgroup III geminiviruses can complement mutations in hete;ologous viral genomes both in protoplasts [10] and in plants [ i 1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic analysis has shown that the organization and function of the ORFs in PYMV and TGMV are similar * Author for correspondence. Fax +44 171 584 2056. e-mail r.coutts@ic.ac.uk (Sung & Coutts, 1995) and places the two viruses in the same phylogenetic cluster (Arguello-Astorga et al, 1994;Faria et al, 1994;Fontes et al, 1994a, b;Padidam et al, 1995). The DNA A components of both viruses encode all of the viral information necessary for replication [the AC 1, protein] and encapsidation (the AV1, coat protein) of both DNAs (Rogers et al, 1986;Sunter et al, 1987;Sung & Coutts, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Fax +44 171 584 2056. e-mail r.coutts@ic.ac.uk (Sung & Coutts, 1995) and places the two viruses in the same phylogenetic cluster (Arguello-Astorga et al, 1994;Faria et al, 1994;Fontes et al, 1994a, b;Padidam et al, 1995). The DNA A components of both viruses encode all of the viral information necessary for replication [the AC 1, protein] and encapsidation (the AV1, coat protein) of both DNAs (Rogers et al, 1986;Sunter et al, 1987;Sung & Coutts, 1995). The protein encoded by the AC30RF, while not absolutely required for viral replication, is necessary for normal accumulation of viral DNA in infected plants (Elmer et al, 1988;Sung & Coutts, 1995) and protoplasts (Sunter et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations